Brown trout Salmo trutta redd superimposition by spawning Lampetra species in a lowland stream - N. Nika; T. Virbickas (Journal of Fish Biology, 2010)
Reproductive interaction between sympatric lampreys and salmonids was studied. The superimposition of brown trout Salmo trutta redds by spring‐spawning river lamprey Lampetra fluviatilis and brook lamprey Lampetra planeri was examined in a small lowland stream of western Lithuania. A high superimposition rate of S. trutta redds by both L. fluviatilis (up to 83%) and L. planeri (up to 48%) was found, when the spawning intensity of Lampetra spp. was high. The occurrence of this phenomenon is the result of the overlap in the spawning habitat preferences at the reach‐scale and at the microhabitat scale for the three species. One of the main requirements for Lampetra spp. spawning site selection was the negative streambed slope, an essential trait of the pool–riffle transitional zone. The structure of the salmonid redd created a considerable negative microhabitat slope suitable for Lampetra spp. spawning, which put the redds under a higher susceptibility to be superimposed. The timing of Lampetra spp. spawning overlapped closely with the emergence of S. trutta fry, suggesting a probable ecological effect of superimposition on S. trutta in the pre‐emergent and emerging stages.

Challenges in developing fish‐based ecological assessment methods for large floodplain rivers - J. J. DE LEEUW; A. D. BUIJSE; G. HAIDVOGL; M. LAPINSKA; R. NOBLE; R. REPECKA; T. VIRBICKAS; W. WIŚNIEWOLSKI; C. WOLTER (Fisheries Management and Ecology, 2007)
Large European floodplain rivers have a great diversity in habitats and fish fauna, but tend to be heavily modified. The complexity of these river systems and their multiple human impacts pose considerable challenges for assessment of their ecological status. This paper discusses: (1) the application of historical information on fish fauna and habitat availability to describe reference conditions; (2) responses of fish assemblages to human disturbance by comparing various rivers and river segments with different impacts and/or time series within rivers; (3) the role of floodplain water bodies in ecological assessment; and (4) monitoring of large rivers using different gears and sampling designs for main channels and floodplain habitats. The challenge for the future is to standardise and calibrate sampling methods and data to enhance the potential for ecological assessment of large rivers.

Development of fish‐based assessment method for the ecological status of rivers in the Baltic region - T. VIRBICKAS; V. KESMINAS (Fisheries Management and Ecology, 2007)
A fish‐based assessment method for determining the ecological status of rivers in the southern part of the Baltic region was developed, classifying fish assemblages of near natural sites, and testing the response of a wide range of fish metrics to human pressure. However, the potential for developing a statistically robust method was limited because of insufficient data and the impact of fishery exploitation. A combination of expert judgement, historical data and spatially based methods were needed to establish reference conditions and classification criteria for fish metrics. The final list of metrics (6–9 metrics per six different river types) comprises five ecological guilds (feeding, overall tolerance, habitat, migration and spawning strategy) and three sentinel (dominant) species ( Salmo trutta L., Cottus gobio L. and Alburnoides bipunctatus [Bloch]). The method tends to underscore the ecological status of specific river types because the selected metrics probably do not account for all possible variability in fish community response to degradation, as some community‐specific characteristics were poorly or not represented. Exploitation pressure might have considerable effects on functionality of fish metrics. Results suggest that the method needs modification to account for these limitations.

Spatially based methods to assess the ecological status of riverine fish assemblages in European ecoregions - S. SCHMUTZ; A. MELCHER; C. FRANGEZ; G. HAIDVOGL; U. BEIER; J. BÖHMER; J. BREINE; I. SIMOENS; N. CAIOLA; A. DE SOSTOA; M. T. FERREIRA; J. OLIVEIRA; et al. (Fisheries Management and Ecology, 2007)
The objective was to develop spatially based (type‐specific) methods to assess the ecological status of European rivers according to the EU Water Framework Directive. Some 15 000 samples from about 8000 sites were pre‐classified within a five‐tiered classification system based on hydromorphological and physico‐chemical pressures. The pre‐classification was used to identify reference conditions and to calibrate the assessment methods. Clustering reference sites based on relative species composition resulted in 60 fish assemblage types within 11 of the ecoregions under study. Discriminant function analyses (DFAs) were employed to identify environmental parameters characterising fish assemblage types; altitude, river slope, wetted width, mean air temperature and distance from source were the principal predictors. These environmental parameters were used to assign impacted sites with altered fish assemblage composition to the reference fish assemblage type. Metrics (fish assemblage descriptors) responding to human pressures were selected based on correlation and DFAs. Assessment methods were developed for 43 fish assemblage types. Metrics based on individual sentinel species were more often used in type‐specific methods than metrics related to reproduction, habitat and feeding. Metrics based on long‐distance migrants and potamodromous species were more sensitive to human pressures than overall composition metrics, e.g. total number of species. Only some of the tested metrics showed pressure‐specific responses, i.e. reacted to one type of pressure but not to others. Insectivorous, intolerant and lithophilic species exclusively responded (decreased) to chemical and hydromorphological pressures in 14–19%. Omnivorous species was the only metric type that showed a consistent reaction (increase) to continuum disruptions in 25% of the cases. Accuracy of methods based on cross‐validation with pre‐classification varied between 47% and 98% (mean 81%) when contrasting calibration data set (class 1 and 2) with degraded sites (class 3, 4 and 5).

Application of an adapted index of biotic integrity to rivers of Lithuania - V. Kesminas; T. Virbickas (Hydrobiologia, 2000)